HyDeploy: The UK's First Hydrogen Blending Deployment Project. Issue 2 (9th May 2019) - Isaac, Tommy
Abstract: The HyDeploy project is the UK's first practical project to demonstrate that hydrogen can be safely blended into the natural-gas distribution system without requiring changes to appliances and the associated disruption. The project is funded under Ofgem's Network Innovation Competition and is a collaboration between Cadent Gas, Northern Gas Networks, Progressive Energy Ltd, Keele University (Keele), Health & Safety Laboratory and ITM Power. Cadent and Northern Gas Networks are the Gas Distribution Network sponsors of the project. Keele University is the host site, providing the gas-distribution network, which will receive the hydrogen blend. Keele University is the largest campus university in the UK. Health & Safety Laboratory provides the scientific laboratories and experimental expertise. ITM Power provides the electrolyser that produces the hydrogen. Progressive Energy Ltd is the project developer and project manager. HyDeploy is structured into three distinct phases. The first is an extensive technical programme to establish the necessary detailed evidence base in support of an application to the Health & Safety Executive for Exemption to Schedule 3 of the Gas Safety (Management) Regulations (GS(M)R) to permit the injection of hydrogen at 20 mol%. This is required to allow hydrogen to be blended into a natural-gas supply above the current British limit of 0.1 mol%. The second phase comprises the construction of the electrolyser and grid entry unit, along with the necessary piping and valves, to allow hydrogen to be mixed and injected into the Keele University gas-distribution network and to ensure all necessary training of operatives is conducted before injection. The third phase is the trial itself, which is due to start in the summer of 2019 and last around 10 months. The trial phase also provides an opportunity to undertake further experimental activities related to the operational network to support the pathway to full deployment of blended gas. The outcome of HyDeploy is principally developing the initial evidence base that hydrogen can be blended into a UK operational natural-gas network without disruption to customers and without prejudicing the safety of end users. If deployed at scale, hydrogen blending at 20 mol% would unlock 29 TWh pa of decarbonized heat and provide a route map for deeper savings. The equivalent carbon savings of a national roll-out of a 20-mol% hydrogen blend would be to remove 2.5 million cars from the road. HyDeploy is a seminal UK project for the decarbonization of the gas grid via hydrogen deployment and will provide the first stepping stone for setting technical, operational and regulatory precedents of the hydrogen vector.